Compressive radial neuropathy induced by 'hooking' manoeuvre in a tetraplegic person - Julia, P.E.; Mazlina, M.; Nazirah, H. (2011)
Study design: Case report. Objective: To describe a case of radial nerve compression neuropathy caused by a common wheelchair technique (hooking manoeuvre) used by a tetraplegic person to maintain truncal stability on a wheelchair. Setting: Department of Rehabilitation Medicine, University of Malaya Medical Centre, Kuala Lumpur, Malaysia. Method and results: A 45-year-old man with American Spinal Injury Association Impairment Scale A C6 for the last 32 years developed progressive weakness of the right upper limb that was associated with pain in the shoulder and arm. Serial physical examinations demonstrated motor and sensory deterioration. Magnetic resonance imaging of the spinal cord showed no evidence of syringomyelia. Electrodiagnostic study showed motor and sensory neuropathy of the right radial nerve in the axillary region. Conclusion: The act of hooking the arm behind the wheelchair push handle causes trauma leading to radial nerve compression neuropathy. Because this technique is used frequently by wheelchair users, future studies should examine the prevalence of radial neuropathy in this population and develop alternative methods to maintain balance on the wheelchair. Spinal Cord (2011) 49, 1082-1083; doi:10.1038/sc.2010.137; published online 28 September 2010